2018
DOI: 10.1016/j.placenta.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations and risk of placental abruption: A genome-wide association study and meta-analysis of genome-wide association studies

Abstract: We identified several genetic loci and related functions that may play a role in PA risk. Understanding genetic factors underlying pathophysiological mechanisms of PA may facilitate prevention and early diagnostic efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Gene expression knowledge continues to guide scientists in search for what can control the levels of sFLt1 for effective treatment of preeclampsia. For example, ABCC8, KCNJ11, and ADAM12 are other genes implicated during pregnancy in a case of placental abruption [16,17].…”
Section: Placental Multi-omics For Understanding Preeclampsiamentioning
confidence: 99%
See 2 more Smart Citations
“…Gene expression knowledge continues to guide scientists in search for what can control the levels of sFLt1 for effective treatment of preeclampsia. For example, ABCC8, KCNJ11, and ADAM12 are other genes implicated during pregnancy in a case of placental abruption [16,17].…”
Section: Placental Multi-omics For Understanding Preeclampsiamentioning
confidence: 99%
“…Placental Abruption [17,19] | Gestational Diabetes [25] | Asthma in Offspring [52,55] Spearman Rank Correlations Preeclampsia [23,27] | Metabolic Syndrome [45] Post Hoc Analyses Respiratory syncytial virus [4] | Preeclampsia [21,29] | Asthma in Offspring [52] Linear Regression Model (including Mixed Effect Model) Maternal Cardiovascular Adaptation [3] | Preeclampsia [23] | Asthma in Offspring [53] Kaplan-Meier Curve Asthma in Offspring [52,53] Kolmogorov-Smirnov Test Preeclampsia [21] | Gestational Diabetes [26] Principal Component Analysis (PCA) Preeclampsia [12] | Metabolic Dynamics of Timing of Delivery [18] Cox Regression Asthma in Offspring [52,53] Pearson Correlation Coefficient Obesity and Overweight [44] Table 1. Statistical methods and machine learning techniques are used in pregnancy literature.…”
Section: T-testmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional analyses performed by the authors revealed that the majority those genes are connected to trophoblast-like cell interaction, or in the endocrine or cardiovascular systems or cellular function pathways. However, their role still needs further research [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal complications include haemorrhagic shock, coagulopathy and disseminated intravascular coagulation, uterine rupture, renal failure and ischemic necrosis of distal organs. 5,6 Neonatal complications include death and neuro-developmental problems. 7 Clinicians confronted with severe abruption and a live fetus has the dilemma of balancing unstable individual with a possible coagulopathy versus possible risks of increased mortality and severe morbidity to the fetus of delay.…”
Section: Introductionmentioning
confidence: 99%